2014
DOI: 10.1186/s13028-014-0066-y
|View full text |Cite
|
Sign up to set email alerts
|

A treatment study of canine symmetrical onychomadesis (symmetrical lupoid onychodystrophy) comparing fish oil and cyclosporine supplementation in addition to a diet rich in omega-3 fatty acids

Abstract: BackgroundTreatment of symmetrical onychomadesis (symmetrical lupoid onychodystrophy) is a challenging task for dermatologists. The acute phase is characterized by sloughing of claw plates and loose claws have to be removed and secondary infections treated. The goal of long-term treatment is to allow claws to re-grow with normal quality and to achieve life-long lack of recurrence. The aim of this randomized treatment trial was to see if adding fish oil or cyclosporine to a diet rich in omega-3 could improve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 13 publications
(20 reference statements)
0
15
0
2
Order By: Relevance
“…Symmetrical lupoid onychodystrophy (SLO) is another condition of autoimmune etiology that affects multiple dog breeds, such as the bearded collie, Gordon setter, English setter, giant schnauzer, Labrador retriever, Welsh corgi, boxer, and German shorthair pointer with variable prevalence (OMIA 001989–9615) [11, 2125]. SLO is a clinical syndrome characterized by sloughing claws and secondary bacterial infection that was first described in 1992 [24, 26, 27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symmetrical lupoid onychodystrophy (SLO) is another condition of autoimmune etiology that affects multiple dog breeds, such as the bearded collie, Gordon setter, English setter, giant schnauzer, Labrador retriever, Welsh corgi, boxer, and German shorthair pointer with variable prevalence (OMIA 001989–9615) [11, 2125]. SLO is a clinical syndrome characterized by sloughing claws and secondary bacterial infection that was first described in 1992 [24, 26, 27].…”
Section: Introductionmentioning
confidence: 99%
“…SLO is a clinical syndrome characterized by sloughing claws and secondary bacterial infection that was first described in 1992 [24, 26, 27]. Since then, most research has focused on disease diagnosis and treatment [22, 25]. While little research exists on the cause of SLO, Wilbe et al [24] and Dahlgren et al [28] have reported an association with particular major histocompatibility complex (MHC; or Dog Leukocyte Antigen, DLA) class II alleles in bearded collies, giant schnauzers, and English and Gordon setters [24, 28].…”
Section: Introductionmentioning
confidence: 99%
“…The growth cycle of dog nails is long (they grow on average 1.9 mm per week), and therefore, 6 to 8 months of treatment is necessary to correct any abnormality (Warren, 2013b). Different studies have used 4-to 6-month-long follow-up periods (Auxilia et al, 2001;Ziener & Nødtvedt, 2014). The follow-up in our case (15 months) seems to have been long enough.…”
Section: Discussionmentioning
confidence: 81%
“…In another study, symptoms improved in 12 onychodystrophic dogs that were fed Eukanuba Veterinary Diets (EVD) Dermatosis® exclusively for 6 months. There was no evidence of better improvement whether cyclosporine or fish oil were added to the diet (Ziener & Nødtvedt, 2014). In that study, vitamin E as a component of fish oil was added to the diet together with omega-3 fatty acids (10 mg of vitamin E per dog daily) (Ziener & Nødtvedt, 2014).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation